How safe is internal iliac artery embolisation prior to EVAR? A 10-year retrospective review. (November 2016) - McGarry, J.; Alenezi, A.; McGrath, F.; Given, M.; Keeling, A.; Moneley, D.; Leahy, A.; Lee, M.
Abstract Purpose Internal iliac artery (IIA) embolisation is commonly performed prior to endovascular aneurysm repair (EVAR) of aortoiliac aneurysms to prevent type 2 endoleaks via the internal iliac arteries. The safety of this procedure is controversial due to the high incidence of pelvic ischaemic complications. Methods We undertook a retrospective review of all patients undergoing IIA embolisation before EVAR from 2002 to 2012, to determine incidence of, and factors associated with pelvic ischaemia. Results Eight of 25 patients (32 %) experienced new-onset ischaemia, including erectile dysfunction (4 %), and buttock claudication (28 %) that persisted >6 months in only four patients (16 %). Both bilateral IIA embolisation and a shorter time interval to EVAR correlate with increased risk (p = 0.006 andp = 0.044). No co-morbidities or demographic factors were predictive. Conclusions We conclude that IIA embolisation remains a beneficial procedure, however, to minimise the risk of buttock claudication we advise against both bilateral IIA embolisation and short time intervals between embolisation and subsequent EVAR.